Identifikasi Sistem Panas Bumi Daerah Cangar, Jawa Timur menggunakan Metode Magnetotelurik - Rahmawati Rahmawati; Sukir Maryanto; Adi Susilo (Universitas Negeri Malang, 2017)
The research has been done in Cangar area of complex Mt.Arjuno-Welirang, East Java. This research using magnetotelluric method. The purpose of this research is to identify the geothermal system of research area based on its resistivity value. Acquisition of magnetotelluric data done in 11 point with spaces 70 meters up to 150 meters. Magnetotelluric measurement points is divided into 5 profile. Based on the result of data processing given range resisitivity value in research area between 4 W.m up to 2000 W.m. The result of modeling geothermal system in Cangar indicated of caprock (≤21 W.m), reservoir (21 W.m – 167 W.m) and a heat source (≥167 W.m). Geothermal Cangar is controlled by Cangar fault.